Cold Flashes : Literary Snapshots of Alaska - Engelhard, Michael, 1959- (Book collections on Project MUSE., 2010)
As the old adage goes, ""if you can't say it in a few pages, you won't in a hundred."" The selections in Cold Flashes-very short prose and black-and-white photographs-embody perfectly this transparency, thrift, and restraint. Found here are highly polished micro-narratives, both fiction and nonfiction, and a series of eloquent and artistic halftones that capture their sizeable subjects in a nutshell. By minimizing the exposition, the selections stimulate the imagination to reflect on the rich diversity of people and places that make up Alaska. To be savored piecemeal at coffee shops, on the bu.